Assessing the Left Ventricular Systolic Function at the Bedside: The Role of Transpulmonary Thermodilution-Derived Indices. (27th July 2011) - Aguilar, Gerardo; Belda, F. Javier; Ferrando, Carlos; Jover, José Luis
Abstract : Evaluating the systolic function of the left ventricle (LV) is important in the hemodynamic management of the critically ill patients with circulatory failure. Echocardiography is considered the standard monitor for estimating the LV function at the bedside in the intensive care unit. However, it requires a trained operator and is not a real-time monitoring tool. For monitoring of the systolic function, the pulmonary artery catheter has been the gold standard for a long time. However, now there are alternatives to this device, with transpulmonary thermodilution being one of them. This paper provides an overview of the usefulness of the transpulmonary thermodilution-derived indices for assessing systolic function at the bedside.